THE CORRELATION BETWEEN READING HABIT AND READING COMPREHENSION ACHIEVEMENT OF 12TH GRADE STUDENTS OF MA. PP. QODRATULLAH LANGKAN - WAHYUDI, AGUS (Sriwijaya University Learning and Education International Conference, 2016)
The main objectives of this study are to find out; 1) how is the studentsâ readinghabit, 2) how is the studentsâ reading comprehenaion achievement, 3) is there anysignificant correlation between reading habit and reading comprehension of 12thgrade students of MA. PP. Qodratullah. The writer used descriptive quantitatifdesign to describe the data. The population of the study was five classes of 12thgrade students of MA. PP. Qodratullah. The sample of this study was 168 students.The writer used questionnaire (Janthong, 2010) and reading test to collect the data.The test was administered once as post-test. Before the post-test was administered tothe sample students, the validity and reliability of the instruments were estimated.The result of the test were analyzed by using Pearson Product Moment in SPSS(Statistical Package for Social Science) 16.0. From the analysis, it was showed thatthe t-obtained was 0.309. It could be concluded that there was no significancecorrelation between the two variables since the t-obtained was higher than 0.05. Thefactors that influnced this condition were; 1) the misperception of the studentstoward good reading habits, 2) students preferred to read for pleasure (comics,newspapers, sport magazines), 3) the students preferred to read for pleasure, whilethe tests of this research were taken from reading for academic purpose materials.However, building a good reading habit is essential to be recommended because it isvery important to develop the studentsâ reading comprehension achievement.